Prevalence of protective level of hepatitis B antibody 3 years after revaccination in HIV-infected children on antiretroviral therapy - Mongkol Lao-araya (2018)
After responding to highly active antiretroviral therapy (HAART), HIV-infected children had a good response to hepatitis B immunization. However, there are limited data on the durability of antibody to hepatitis B surface antigen (anti-HBs) in these children. The primary objective of this study is to determine the prevalence of protective anti-HBs level 3 years after a 3-dose HBV revaccination among HIV-infected children with immune recovery (CD4 cell ≥15%) while on HAART. The secondary objective is to assess immunologic memory among children who had waning of anti-HBs. An anti-HBs level of ≥10mIU/mL was defined as a protective antibody level. Sixty-nine HIV-infected children who had history of a 3-dose HBV revaccination while receiving HAART were enrolled. The mean (SD) of CD4 cell and duration of HAART at time of revaccination was 27.2% (6.7) and 5.9 years (0.4), respectively. The proportion of children with protective anti-HBs level 3 years after the revaccination was 71.0% [95% CI, 58.8-81.3]. The geometric mean titer was 114(SD 5)IU/mL. By multivariate logistic analysis, the predictors for protective anti-HBs level 3 years after revaccination were CD4 cell count ≥500cells/mm3at the time of vaccination (p=0.04) and anti-HBs level ≥100IU/mL at 1 month after completion of the 3-dose vaccination (p<0.001). Anamnestic response after one booster dose was demonstrated among 14 of 17 children who had waning protective anti-HBs level (82.4% [95% CI, 62.2-102.6]). Our findings support the recommendation of giving a 3-dose HBV vaccination to HIV-infected children with immune recovery while receiving HAART. © 2011 Elsevier Ltd.